2019
DOI: 10.1093/ibd/izz071
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Vedolizumab Utilization Across US Academic Centers and Community Practice Are Associated With Improved Effectiveness and Disease Outcomes

Abstract: BackgroundVedolizumab effectiveness estimates immediately after Food and Drug Administration (FDA) approval for ulcerative colitis (UC) and Crohn’s disease (CD) are limited by use in refractory populations. We aimed to compare treatment patterns and outcomes of vedolizumab in 2 time frames after FDA approval.MethodsWe used 2 data sets for time trend analysis, an academic multicenter vedolizumab consortium (VICTORY) and the Truven MarketScan database, and 2 time periods, May 2014–June 2015 (Era 1) and July 2015… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 13 publications
2
9
1
Order By: Relevance
“…The remission rates reported in adult studies are higher than the rates observed in the children in our cohort (17,24), which may be explained by inclusion of anti-TNF refractory PIBD patients only, whereas this was not the case in the adult studies. This is supported by studies showing significantly better outcomes in anti-TNF-naïve IBD patients (25)(26)(27) explanation for loss of response to anti-TNF, our data do not suggest that nonresponse or loss of response to VDZ can be explained by the formation of antibodies to VDZ (28). This is consistent with studies in adults that indicate immunogenicity to occur in <5% of cases (17,29).…”
Section: Discussionsupporting
confidence: 91%
“…The remission rates reported in adult studies are higher than the rates observed in the children in our cohort (17,24), which may be explained by inclusion of anti-TNF refractory PIBD patients only, whereas this was not the case in the adult studies. This is supported by studies showing significantly better outcomes in anti-TNF-naïve IBD patients (25)(26)(27) explanation for loss of response to anti-TNF, our data do not suggest that nonresponse or loss of response to VDZ can be explained by the formation of antibodies to VDZ (28). This is consistent with studies in adults that indicate immunogenicity to occur in <5% of cases (17,29).…”
Section: Discussionsupporting
confidence: 91%
“…Prior work from our group has observed that inflammatory bowel disease patients treated with vedolizumab early after its approval and availability in the market were more refractory and had lower persistence rates compared to more recent utilisation. 37 Therefore, it's possible that these differences were related to utilisation patterns in which vedolizumab-treated patients earlier in the period were simply more refractory requiring early discontinuation and those treated later in the observation period had less time to be exposed to the drug.…”
Section: Discussionmentioning
confidence: 99%
“…The 12-month analysis (b) included data reported from 52 weeks to 13.5 months. Cumulative rates from ERA 2 of the VICTORY trial reported by Koliani-Pace [49] were higher than those observed for other studies included in this meta-analysis. Endpoint definitions: absence of ulcers/erosions and/or Simple Endoscopic Score for Crohn's Disease cut − points < 4 (Table 2).…”
Section: Discussioncontrasting
confidence: 75%
“…In the VER-SIFY phase 3b clinical trial, rates of endoscopic remission (SES-CD score of ≤ 4) and endoscopic response (≥50% reduction in baseline SES-CD score) at 52 weeks (n = 101) : Meta-analysis results: secondary analysis. Faleck [54], Plevris [43], and Koliani-Pace [49] reported cumulative rates; other studies reported point estimates. The 6-month analysis (a) included data reported from 22 to 30 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation